Reward enhances resilience to chronic social defeat stress in mice: Neural ECs and mGluR5 mechanism via neuroprotection in VTA and DRN - Shi, Peixia; Hu, Linlin; Ren, Hui; Dai, Qin (Frontiers in psychiatry, 2023)
Stress often leads to emotional disorders such as depression. The reward might render this effect through the enhancement of stress resilience. However, the effect of reward on stress resilience under different intensities of stress needs more evidence, and its potential neural mechanism has been poorly revealed. It has been reported that the endogenous cannabinoid system (ECs) and downstream metabolic glutamate receptor 5 (mGluR5) are closely related to stress and reward, which might be the potential cerebral mechanism between reward and stress resilience, but there is a lack of direct evidence. This study aims to observe the effect of reward on stress resilience under different intensities of stress and further explore potential cerebral mechanisms underlying this effect. Using the chronic social defeat stress model, we applied reward (accompanied by a female mouse) under different intensities of stress in mice during the modeling process. The impact of reward on stress resilience and the potential cerebral mechanism were observed after modeling through behavioral tests and biomolecules. The results showed that stronger stress led to higher degrees of depression-like behavior. Reward reduced depression-like behavior and enhanced stress resilience (all -value <0.05) (more social interaction in the social test, less immobility time in the forced swimming test, etc.), with a stronger effect under the large stress. Furthermore, the mRNA expression levels of CB1 and mGluR5, the protein expression level of mGluR5, and the expression level of 2-AG (2-arachidonoylglycerol) in both ventral tegmental area (VTA) and dorsal raphe nucleus (DRN) were significantly upregulated by reward after modeling (all -value <0.05). However, the protein expression of CB1 in VTA and DRN and the expression of AEA (anandamide) in VTA did not differ significantly between groups. Intraperitoneal injection of a CB1 agonist (URB-597) during social defeat stress significantly reduced depression-like behavior compared with a CB1 inhibitor (AM251) (all -value <0.05). Interestingly, in DRN, the expression of AEA in the stress group was lower than that of the control group, with or without reward (all -value <0.05). These findings demonstrate that combined social and sexual reward has a positive effect on stress resilience during chronic social defeat stress, potentially by influencing the ECs and mGluR5 in VTA and DRN.